Evaluation of Electronic Health Literacy Level of Patients Referring to a Selected Military Hospital in Tehran - Mahdi Isazadeh; Zahra Sadat Asadi; Mahdi Tahmasebi Gharajehmalek; Manijeh Soleimanifar (Tehran University of Medical Sciences, 2020)
Background and Aim: Currently, electronic health(e-health) tools are known as an effective means of communication and educational tool in the field of health to manage conditions in sensitive situations. The purpose of this study was to evaluate the level of electronic health literacy of patients referring to a selected military hospital. Materials and Methods: The present descriptive-analytical study was performed on 204 patients who referred to a selected military hospital in Tehran in 2019. Data collection tools included a demographic information questionnaire and an e-health literacy questionnaire. SPSS software was used for data analysis, and the level of significance was set at 0.05. Results: The mean score of electronic health literacy was 29.28±5.47. The level of e-health literacy of patients with different educational backgrounds was significantly different. Also, the electronic health literacy of patients using the Internet differed significantly. Patientschr('39') e-health literacy had a significant correlation with their educational level(p=0.02, r =0.169) and using the Internet(p<0.001, r=0.328). Conclusion: Higher education is associated with higher levels of e-health literacy, and can be improved by creating internet training areas to access health information to improve e-health literacy.